Longevity and gender as the risk factors of methicillin-resistant Staphylococcus aureus infections in southern Poland - Pomorska-Wesołowska, Monika (BMC Geriatr, 2017)
BACKGROUND: The proportion of older people among the general population has risen. Staphylococcus aureus (SA) constitutes a significant problem. Underlying disease and functional debility, predispose the older adult to staphylococcal carriage and infection, specially bloodstream infection and pneumonia. METHODS: This is a retrospective cohort study of older patients with SA infections. We analyzed a database containing the results of laboratory cultures from patients treated in 2013 for SA infections and selected 613 hospitalized and non-hospitalized people aged ≥60 years. RESULTS: The prevalence of Methicillin-resistant SA (MRSA) were significantly different in categories of patients: from 14.1% in young old, 19.5% in old old and 26.7 in longevity. MRSA was significantly more frequently reported in cases of pneumonia, 40.4% of SA strains (p < 0.0001, OR 0.3, 95%CI 0.14–0.49). The nosocomial MRSA infections were more common in ICU departments: prevalence 36.8%, than in non-ICU departments: prevalence 17.3% (OR 2.8, 95%CI 1.06–7.34, p = 0.014). Bloodstream infections, which accounted for 6% of all infections, were more frequent in males (p = 0.0231, OR 2.25, 95%CI 1.098–4.604). The greatest increase in antibiotic resistance was related to trimethoprim/sulfamethoxazole (TMP/SXT), which increased to over 80% in the older study groups. All age groups demonstrated increased MIC90 values for glycopeptide and tigecycline. Although strains isolated from patients in all age groups remained sensitive to vancomycin, strains isolated from patients in the old-old and longevity groups demonstrated resistance to teicoplanin. The MIC90 for tigecycline was the highest in the group aged >90 years. CONCLUSIONS: MRSA constitutes a significant epidemiological problem in cases of hospital-treated pneumonia. The findings were similar for long-term-care facilities, where MRSA appears to affect male residents in particular, although there were fewer male residents than female residents. The low sensitivity to TMP/SXT of SA strains isolated from the oldest patients indicates potentially serious challenges pertaining to efficacious treatment of SA infections.